Catheter ablation in adults with congenital heart disease: a 15-year perspective from a tertiary center. (25th November 2020) - Waldmann, V; Amet, D; Zhao, A; Ladouceur, M; Karsenty, C; Maltret, A; Pontnau, F; Legendre, A; Soulat, G; Lavergne, T; Bonnet, D; Jouven, X; et al.
Abstract: Background: With the growing population of adults with congenital heart disease (ACHD), the number of catheter ablation procedures is expected to increase over time. Purpose: We aimed to describe temporal trends in volume and outcomes of catheter ablation procedures in ACHD patients in a large tertiary center. Methods: Retrospective observational study including all consecutive ACHD patients undergoing catheter ablation in a tertiary reference center over a 15-year period. Acute procedural success rate (including complete success in case of non-inducibility of any arrhythmia at the end of the procedure) as well as freedom from recurrence at 12 months were analyzed. Results: From November 2004 to November 2019, 302 catheter ablations in 221 ACHD patients (43.6±15.0 years, 58.9% males) were performed. The annual number of catheter ablation increased progressively from 4 to 60 by year (p<0.001). Intra-atrial reentrant tachycardia/focal atrial tachycardia was the most common targeted arrhythmia (n=217, 71.9%). Over the study period, acute procedural success rate increased from 45.0% to 93.3% (p<0.001), including complete acute procedural success from 45.0% to 88.1% (p<0.001) (Figure 1). The use of irrigated catheters (30.0% to 94.8%, p<0.001), 3D-mapping systems (60.0% to 96.3%, p<0.001), contact force catheters (0.0% to 91.9%, <0.001), and high-density mapping (0.0% to 71.9%, p<0.01) increased significantly. Use of irrigated catheters (OR=3.96, 95% CI: 1.79–8.55), 3D-mapping system (OR=3.55, 95% CI: 1.62–7.55), contact force catheters (OR=3.46, 95% CI: 1.71–7.25), and high-density mapping (OR=3.85, 95% CI: 1.60–7.26) were associated with acute procedural success. The rate of freedom from any recurrence at 12 months increased from 29.4% to 66.2% (p=0.001). Seven (2.3%) non-fatal complications occurred. Conclusions: The number of catheter ablation procedures in ACHD patients has considerably increased over the last 15 years. Advances in ablative technologies appear to be associated with a low rate of complications and a significant improvement in acute and midterm outcomes. Funding Acknowledgement: Type of funding source: None